Profile of Stroke Patients in John Piet Wanane General Hospital Sorong: A Descriptive Study - Djohan Ardiansyah; Agustinus Ruma; Lu Jordy Luhur (Universitas Airlangga, 2025)
Highlight: Hypertension is the leading risk factor for cardiovascular disease and stroke. Blood pressure variability, including early morning surge, increases stroke risk. Low education is associated with an increased risk of stroke due to limited health literact and lifestyle challenges. ABSTRACT Introduction: Stroke has become the major cause of physical disability in adults and the second leading cause of death in middle- to high-income countries. Indonesia has the second-highest mortality rate and stroke burden in Southeast Asia. Furthermore, there is limited study on stroke in eastern Indonesia, especially in Papua. Objective: This study aimed to evaluate the clinical profile of stroke patients treated in John Piet Wanane General Hospital. Methods: This descriptive, hospital-based study was conducted at John Piet Wanane General Hospital, Sorong, Southwest Papua, from August 1, 2023, to January 31, 2024. Data were collected through interviews and the identification of subjects’ medical records based on inclusion and exclusion criteria. Results: This study involved a total of 143 patients, with an average age of 58.17 ± 10.516 years. The gender distribution was nearly equal, with 52.4% women and 47.6% men. The subjects mainly had an overweight Body Mass Index (BMI) (39,2%) or a normal BMI (36.4%). Obesity and underweight were the least common with percentage of 18.9%% and 5.6% of subjects, respectively. Hypertension (75.5%), prior stroke (33.6%), and hyperlipidemia (33.6%) were the most frequently found among subjects. Diabetes mellitus was found in 29.4% of subects, followed by smoking (28.7%), a history of heart disease (21%), and alcohol consumption (14.7%). Ischemic stroke was the most prevalent type of stroke (65.7%), followed by intracerebral hemorrhage (23,8%), transient ishcemic attack (TIA) (5.6%), subarachnoid hemorrhage (2.8%), and pontine hemorrhage (2.1%). Conclusion:This study revealed that ischemic stroke was the predominant subtype, while pontine hemorrhage was rare. Hypertension emerged as the most common risk factor, followed by prior stroke, hyperlipidemia, and diabetes mellitus, highlighting the substantial burden of modifiable vascular risk factors.